Optimalisasi Penurunan Kehilangan Air Di Zona Pelayanan Perusahaan Umum Daerah Air Minum - Barikiyah, Saeril; Masduqi, Ali (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
According to Regulation of the Ministry of Public Works and Housing of the Republic of Indonesia No. 27/PRT/M/2016, the maximum allowable level of non-revenue water (NRW) in a drinking water supply system (DWSS) is 20%. However, the NRW level of a regional water utility (Perumdam) in East Java has reached 26.47%, consisting of a total distributed water volume of 5,922,337 m³ and a billed water volume of 4,354,472.00 m³. One of the causes of this NRW is the distribution pipeline network system, which remains interconnected between different networks. This study aims to analyze the optimization of NRW reduction, particularly in one service zone. The research method used is an analysis of the existing conditions and NRW control using Epanet software. Based on the research findings, it was identified that all customers in the service zone met the minimum pressure requirement of 5–10 m. Water loss control was carried out through the establishment of a District Metered Area (DMA), optimization of the pipeline network, active leakage control, and pressure management. The results showed a reduction in physical water loss by 0.86%, with a saved water volume of 20,571 m³ per month.